Production of Biodiesel from Candlenut Seed Oil (Aleurites Moluccana Wild) Using a NaOH/CaO/Ca Catalyst with Microwave Heating - Elfrida Siregar; Lisnawaty Simatupang; Jhony Hartanta Sembiring; Elfrida Ginting (Jurnal Kimia Sains dan Aplikasi, 2024)
Oil fuels derived from fossils are non-renewable, so over time, they will run out and have a negative impact on air pollution. To overcome this, there is a need for environmentally friendly alternative fuels from renewable sources such as biodiesel. This research used microwave heating with a CaO catalyst. NaOH-impregnated snail shells and active carbon support. This research aims to determine the effect of power on the conversion of candlenut seed oil into biodiesel using the NaOH/CaO/CA catalyst both in terms of compliance with the SNI 7182-2015 standard and analysis using GC-MS (Gas Chromatography-Mass Spectrometry). The synthesis of the NaOH/CaO/CA catalyst was carried out through wet impregnation and calcination at a temperature of 500°C and analyzed using gas sorption analysis (GSA). Then proceed to the transesterification process, where the power for microwave heating was varied to 300, 450, and 600 watts with a mole ratio of esterified oil and methanol, namely 1:10 for 3 minutes. The analysis results of the NaOH/CaO/CA catalyst using the GSA instrument have a surface area of 9.306 m2/g, pore volume of 0.033 cc/g, and pore diameter of 14.043 nm. Meanwhile, the results of the biodiesel analysis showed that the optimum biodiesel yield was 85.625% at 600 watts of power and had a kinematic density and viscosity that met the SNI 7182-2015 biodiesel standards. Analysis of biodiesel characteristics using GC-MS showed that the three most optimum biodiesel components were hexadecanoic acid, methyl ester (22.664%), 9,12-Octadedecadienoic acid (Z,Z)-, methyl ester (30.176%) and 9-Octadecenoic acid (Z)-, methyl ester (38.656%).